Sustainable development of environment and energy aspects of methane fermentation on family farms in Poland - J. Barwicki; A. Marczuk; D. Góral; M. Góral-Kowalczyk; S. Nazarewicz (Аграрная наука Евро-Северо-Востока, 2022)
The goal of these study was to present results of investigation concerning possibilities of utilization of harmful wastes in countryside area to produce ecological energy. Biogas production can be important from the point of view of environment protection especially in case of overproduction of animal wastes. Production and utilization of energy from agriculture residues gives a great chance for diversification and grows of income for family farms. Besides energetic and environment gains, we can obtain very valuable fertilizer, which is easy absorbed by plants in field crop production. The experimental study was conducted to investigate the effect of mixing process on the parameters of methane fermentation process. Temperature inside fermentation chamber, pH of fermented material, redox potential and carbon to nitrogen ratio (C:N) were investigated. Utilize wastes from pig and poultry houses were used for the study. Digestion in a chamber was provided at constant temperature of 37 °C. After adding fresh substrate to the digester, the temperature of the raw material decreased by 1,0-1.5 °C depending on the location in the tank. Also, it was observed that biogas production decreased. The mixing process had a positive effect on the homogeneity of the material throughout the digester volume. The best results for biogas production were obtained when the pH value was 7.0. Research results obtained from tested biogas installation show, that from two bio reactors at total capacity of 410 m3 we can get electrical energy at cost of 34,52 € MWh-1 and thermal energy at cost of 62,54 €×MWh-1. While the cost of producing electricity in a professional power plant based on lignite was 76.23 €MWh-1. The energy produced was used for the operational activities of the farm.